The influence of thyroid function on arterial hypertension in patients with non-alcoholic fatty liver disease - Telnova, S. (My University, 2013)
The study of peculiarities of AH depending on thyroid function in patients with NAFLD is relevant and will be accompanied by optimization of diagnosis and treatment of hypertension in these patients, given the proliferation of thyroid dysfunction liver pathology and its impact on the progression of cardiometabolic risk factors.
Keywords: arterial hypertension; non-alcoholic fatty liver disease; hypothyroidism